ITB TOUR GUIDE SYSTEM WITH IBEACON - Glendy Wowiling (NIM : 23215031), Rolty
ITB is a campus that has a landscape architecture as it consists of unique campus buildings and has a lot of green open field (green campus). ITB as a technology campus can apply smart campus in their environment and activity. Smart campus means technology, campus infrastructure, and information can be integrated into a system that connected each other (Internet of Things). The combination of IoT and landscape architecture that owned by ITB, can be a special attraction for a place of tourism. ITB university is not only visited by students, lecturers and campus staff but can be visited by the citizen, high school students who have a campus visit and tourists who want to see the beauty and history of ITB. Information and history of some places that located in ITB can use IoT technology to distribute the informations. IBeacon is a small device that contains BLE modules and coin battery as a power, can be used to personalize information in every building. IBeacon emits RSSI signals and proximity so they can be used for detecting an approaching object. This research will use and build a smart campus system using iBeacon, Android app and web service. IBeacon is used as a device that will send the UUID to the app so that the app will display information in pop-up notifications. The system will be built, displays the information from each place that has been installed iBeacon and there is also the information about ads and campus stall feature. System testing is done by retrieval the data in the form of user information, data number of visitor, campus stall order, feedback and rating from users. The system will process data and display information in the form of analysis results through web service applications.